CD90-positive stromal cells associate with inflammatory and fibrotic changes in modic changes. Issue 3 (September 2022) - Dudli, Stefan; Karol, Agnieszka; Giudici, Luca; Heggli, Irina; Laux, Christoph J; Spirig, Jose M; Wanivenhaus, Florian; Betz, Michael; Germann, Christoph; Farshad-Amacker, Nadja; Brunner, Florian; Distler, Oliver; et al.
Abstract: Objective: Modic changes (MC) are vertebral bone marrow lesions seen on magnetic resonance images, that associate with disc degeneration and low back pain (LBP). Few studies described MC histopathology qualitatively based on a few patient samples. CD90-positive bone marrow stromal cells were shown to be pro-fibrotic in MC. We aimed to provide the first semi-quantitative histomorphometric analysis of MC bone marrow. We hypothesized a role of CD90-positive cells in MC pathomechanisms. Design: Human biopsies from Modic type 1 changes (MC1, n ​= ​8), Modic type 2 changes (MC2, n ​= ​6), and control biopsies (MC0, n ​= ​8) from adjacent vertebrae were obtained from 14 LBP patients during lumbar spinal fusion. Biopsies were processed for histology/immunohistochemistry. Inflammatory changes (oedema, inflammatory infiltrates), fibrotic changes (connective tissue, type I and III collagen, fibronectin, α-smooth muscle actin), and amount of bone marrow stromal cells (CD90, CD105) were scored. Scores for MC0, MC1, and MC2 were compared with non-parametric tests. Pairwise correlations, hierarchical clustering, and principal component analysis of histological readouts were calculated to identify most important histomorphometric MC characteristics. Results: Compared to MC0, MC1 had more connective tissue, oedema, inflammatory infiltrates, and CD90 + cells. MC2 compared to MC0 had more oedema and CD90 + cells. Scores of CD90 correlated and clustered with inflammatory and fibrotic changes. Amount of connective tissue correlated with LBP. Conclusion: Accumulation of CD90 + cells is a major characteristic of MC in patients undergoing lumbar spinal fusion and associates with inflammatory and fibrotic changes. Therefore, CD90 + cells may play an important role in the inflammatory-fibrotic pathomechanisms of MC.